2019
DOI: 10.1007/s10803-018-3861-x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Feasibility Trial of Immersive Virtual Reality Treatment with Cognitive Behaviour Therapy for Specific Phobias in Young People with Autism Spectrum Disorder

Abstract: We examined the feasibility and acceptability of using an immersive virtual reality environment (VRE) alongside cognitive behaviour therapy (CBT) for young people with autism experiencing specific phobia. Thirty-two participants were randomised to treatment or control. Treatment involved one session introducing CBT techniques and four VRE sessions, delivered by local clinical therapists. Change in target behaviour was independently rated. Two weeks after treatment, four treatment participants (25%) and no cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 42 publications
1
56
0
1
Order By: Relevance
“…Similar to the use of realistic visual three-dimensional stimuli rendered in VR for desensitisation to specific phobias and environments that may provoke anxiety in individuals with autism [66][67][68], SoundFields produces realistic three-dimensional auditory stimuli that can simulate the movement and acoustic environments of feared sounds. For any form of VRET to be considered successful, the virtual environment must be capable of eliciting emotions such as anxiety in order for new positive associations with the stimuli to be formed through controlled and graduated exposure [69].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the use of realistic visual three-dimensional stimuli rendered in VR for desensitisation to specific phobias and environments that may provoke anxiety in individuals with autism [66][67][68], SoundFields produces realistic three-dimensional auditory stimuli that can simulate the movement and acoustic environments of feared sounds. For any form of VRET to be considered successful, the virtual environment must be capable of eliciting emotions such as anxiety in order for new positive associations with the stimuli to be formed through controlled and graduated exposure [69].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study applied VR exposure therapy to treat specific phobias in 32 autistic children and found that 45% of children remained free from their fears 6 months after the treatment. 33 These results highlight the ability of VR to help autistic children prepare for real-world stressors.…”
Section: Discussionmentioning
confidence: 90%
“…This approach needs to better tailor the VR experiences to the specific coping skills of each child. In a recent randomized controlled trial ( Maskey et al., 2019 ), clinicians used VR to treat autistic children experiencing specific phobias with positive results.…”
Section: Clinical Applications and Recommendations ∗mentioning
confidence: 99%